Open-Mindedness in Action: Thinking Processes in Solving Non-Routine Mathematical Problems - Faradila Thalib; Cholis Sa'dijah; Abdur Rahman As’ari; Tjang Daniel Chandra (Universitas Pendidikan Ganesha, 2025)
Students' thinking skills in dealing with a mathematical problem must be based on critical thinking skills and problem-solving skills. Part of critical thinking skills is disposition (tendency). A person's critical thinking behavior when responding to a problem is based on at least one component of critical thinking disposition, namely open-mindedness. This study aims to investigate the thinking process of students who have open-mindedness through problem solving. We provided information on non-routine mathematical problems to assess students' proficiency in problem-solving. This study employed a descriptive qualitative method with an exploratory design to examine students’ open-mindedness in solving non-routine mathematical problems. Three students, out of a total of 123, were selected as research participants. Data were collected through problem-solving tasks, classroom observations, documentation, and semi-structured interviews supported by audio and video recordings. Data analysis was conducted inductively through the stages of data collection, reduction, presentation, interpretation, and triangulation to ensure the validity of the findings. The results showed that the participants' characteristic of open-mindedness had emerged; they were able to understand non-routine problems and provide solutions in ways that were supported by reasons based on previously obtained knowledge and information. The participants showed emotional intelligence, humility, openness, and tolerance toward each other. As a conclusion, the students need to identify, understand, and be creative when solving non-routine problems. They should respond quickly and carefully using open-mindedness, analyzing multiple solutions based on previous knowledge. They should also demonstrate emotional intelligence, humility, openness, and tolerance.